Discovery of {4-[4, 9-bis(ethyloxy)-1-oxo-1, 3-dihydro-2H-benzo[f]isoindol-2-yl]-2-fluorophenyl}acetic acid (GSK726701A), a novel EP4 receptor partial agonist for the treatment of pain. Issue 10 (1st June 2018) - Healy, Mark P.; Allan, Amanda C.; Bailey, Kristin; Billinton, Andy; Chessell, Iain P.; Clayton, Nicholas M.; Giblin, Gerard M.P.; Kay, Melanie A.; Khaznadar, Tarik; Michel, Anton D.; Naylor, Alan; Price, Helen; et al.
Graphical abstract: Highlights: A novel series of selective and potent EP4 receptor partial agonists identified. GSK726701A has good PK in rat, dog and monkey. Robust activity in a range of animal models of inflammatory and neuropathic pain. Abstract: A novel series of EP4 agonists and antagonists have been identified, and then used to validate their potential in the treatment of inflammatory pain. This paper describes these novel ligands and their activity within a number of pre-clinical models of pain, ultimately leading to the identification of the EP4 partial agonist GSK726701A.